Análise das práticas de preservação de documentos em papel do Arquivo Guilherme De La Penha no Museu Emilio Goeldi - CONCEIÇÃO, William Magno da (2022)
Analysis of paper-based document preservation practices developed at the Guilherme de La Penha Archive, located at the Museu Paraense Emílio Goeldi. We opted for a qualitative approach, using as a collection instrument, bibliographic survey and semi-structured interviews, with the application of 02 forms, respectively the head of the current session of the archive and the technicians who work directly with preservation. It was found that, despite the institution applying localized preservation practices, it is clear that improvements are still needed, and the inclusion of preservation policies and plans and greater public investment are needed.